Attributes of desirable acoustic environments in some rooms - Berglund, B.; Hojan, E.; Furmann, A.; Sworek, K. (Archives of Acoustics, 2002)
Normal hearing native Polish speaking subjects were asked to choose attributes of a desirable acoustic environment, which were presented in a list. The subjects were asked to describe the attributes that would be desirable while listening to a lecture hall, reading a book in a living room and listening to a musical performance in concert hall. Results indicate that the methods used to derive the attributes is valid, that women apply more and slightly different attributes then men and some attributes are uniformly used across the environments tested.